Ensino de filosofia e as TIC: reflexões a partir de experiências do PIBID.Filosofia da UFSM - Moraes, Simone Becher Araujo (2014)
The questions about philosophy teaching and the Information and Communication Technology (ICT), appear in the last years as a concern by teachers and researchers. This research is part of the Research Line 2: School Practices and Public Policy of the Postgraduate Program in Education at the Universidade Federal de Santa Maria (UFSM).The objective of this work is to problematize questions regarding the limits and possibilities of reflecting, discussing and using ICT in the philosophy teaching in high school. The materialities used in this study are: the articles produced by researchers and professors of philosophy teaching that were published in the ten editions of the Simpósio Sul-brasileiro de ensino de filosofia ; some works published by leading philosophers of current technologies, such as Pierre Lévy (1994, 1998, 1999), Paul Virilio (1998, 1999, 2001), among others. Standard-setting documents were also used to bring the results of public policies that guided the problematizations presented here. The main source of discussions on the subject were the reflections produced by scholars who were part of the program: Programa Institucional de Bolsas de Iniciação à Docência (PIBID) in 2012.The scholars developed workshops in two public schools of Santa Maria/RS, about the subject The men and the technology in 21st century . As results of this study, we highlight the evident contribution of the program PIBID.Filosofia of UFSM for the initial and continuing philosophy teaching education. It provides not only contact with the classroom and the practice of teaching but also the movement of thinking philosophically the questions about the reality of the school that is still preserved inside the traditional patterns. Such patterns present certain resistance to the coming of the new and this new youngster who is immersed in the virtual culture. This research is intended to be a contribution to the philosophical discussion about the theme of ICT and the teaching of philosophy.